103Rh NMR shifts of RhI-β-diketonato and RhI-β-aminoketonato complexes influenced by different substituents. (1st September 2019) - Twigge, Linette; Swarts, Jannie C.; Conradie, Jeanet
Graphical abstract: 103 Rh, 1 H and 31 P NMR data of [Rh(β-diketonato)(CO)(PPh3 )], [Rh(CH3 COCHC(NR 2 )CH3 )(CO)(PPh3 )] and [Rh(β-diketonato)(COD)] complexes with β-diketonato = RCOCHCOR 1 and R and/or R 1 = H, CH3, ferrocenyl, phenyl, CF3, thienyl and for the β-aminoketonato R 2 = H or Ph, are reported. The chemical shift values of 103 Rh have been measured by inverse two-dimensional 31 P, 103 Rh- or 1 H, 103 Rh NMR. The chemical shift values are compared to that of similar Rh I -β-diketonato compounds previously reported in literature. It was shown that by changing the electron-density of the β-diketonato or β-aminoketonato ligand, a small change in chemical shift was observed, while by changing from the CO and PPh3 ligands to the less π-acceptor COD ligand, a bigger change in chemical shift occur. Abstract: 103 Rh, 1 H and 31 P NMR data of [Rh(β-diketonato)(CO)(PPh3 )], [Rh(CH3 COCHC(NR 2 )CH3 )(CO)(PPh3 )] and [Rh(β-diketonato)(COD)] complexes with β-diketonato = RCOCHCOR 1 and R and/or R 1 = H, CH3, ferrocenyl, phenyl, CF3, thienyl and for the β-aminoketonato R 2 = H or Ph, are reported. The chemical shift values of 103 Rh have been measured by inverse two-dimensional 31 P, 103 Rh- or 1 H, 103 Rh NMR. Values for 103 Rh of [Rh(β-diketonato)(CO)(PPh3 )] and [Rh(CH3 COCHC(NR 2 )CH3 )(CO)(PPh3 )] varies from 103 to 322 ppm, while 103 Rh values for [Rh(β-diketonato)(COD)] lies between 1286 and 1327 ppm. The chemical shift values are compared to that of similar Rh I -β-diketonato compounds previously reported in literature. It was shown that by changing the electron-density of the β-diketonato or β-aminoketonato ligand, a small change in chemical shift was observed, while by changing from the CO and PPh3 ligands to the less π-acceptor COD ligand, a bigger change in chemical shift occurs.